Literature Review: Relationship of Family Support with the Medication Adherence in Tuberculosis Patients (TB) - Nadya Fickry Martina Suparjo; S. Eko Ch Purnomo; Nina Indriyawati (Poltekkes Kemenkes Semarang, 2020)
Background: Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis. Tuberculosis treatment programs are long and cause some side effects that make patients not adherent to treatment so that family support is needed.Purpose: This study aims to discuss family support with medication adherence in patients with pulmonary tuberculosis.Methods: The type of research that studies the literature using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) method. This literature study took 17 electronic journals from 112 international and national electronic journals namely pubmed, google scholar, and one search published between 2014 and 2019 with research inclusion criteria, namely articles containing family support and medication adherence in patients with pulmonary tuberculosis.Results: Most of the literature states that family support is in the good category and has high medication adherence. The most extended family support given to pulmonary tuberculosis patients is informational support and emotional support, while the least support provided is instrumental support. The most dominant adherence factors are the patient's desire to recover or good patient motivation, the role of the family or good family support, and the role of the health worker as a PMO. The relationship of family support with medication adherence in patients with pulmonary tuberculosis showed a significant relationship.Conclusion: The literature states that the better the family support given to patients with pulmonary tuberculosis, the higher the compliance to take medication for these patients. Family support can improve treatment success in patients with pulmonary TB.